Manifesto of a tenured radical - Nelson, Cary (Cultural front (Series), 1997)
In an age when innovative scholarly work is at an all-time high, the academy itself is being rocked by structural change. Funding is plummeting. Tenure increasingly seems a prospect for only the elite few. Ph. D.'s are going begging for even adjunct work. Into this tumult steps Cary Nelson, with a no- holds-barred account of recent developments in higher education. Eloquent and witty, Manifesto of a Tenured Radical urges academics to apply the theoretical advances of the last twenty years to an analysis of their own practices and standards of behavior. In the process, Nelson offers a devastating critique of current inequities and a detailed proposal for change in the form of A Twelve-Step Program for Academia.